Art and memory: Magdalenas por el Cauca - Neyla Graciela Pardo Abril (Heritage, Memory and Conflict, 2022)
Adopting an interdisciplinary framework of Memory Studies and Art and employing semiotics with a multimodal and multimedia character, it is explored how social groups in Colombia memorialise the violence of the internal armed conflict. The reflection associates the victims’ experiences with those expressions of commemoration and remembrance that are narratives embodied in visual and scenic art. It is explored how a semiotic landscape of memory is created through a performative artistic proposal. In this landscape, not only cultural frames can be determined, but also the semiotic-discursive resources that give meaning to the relationship between art and memory. The aim is to characterise the performance known as Magdalenas por el Cauca (2008) which was recorded audiovisually in several spaces on the internet. It means that, in addition to the ephemeral mise-en-scène, there are records of the performative and communicative work. In this article, we analyse the video X PEREGRINACION TRUJILLO y MAGDALENAS POR EL CAUCA (2010), one of the records that perpetuates Magdalenas por el Cauca. This reparation act is an audiovisual narrative with ethical and political character and produced collectively by relatives of victims, witnesses, artists and other interlocutors, which interpret and assign new meanings to the performance.